2019
DOI: 10.1016/j.cma.2019.04.006
|View full text |Cite
|
Sign up to set email alerts
|

A Fourier-accelerated volume integral method for elastoplastic contact

Abstract: The contact of solids with rough surfaces plays a fundamental role in physical phenomena such as friction, wear, sealing, and thermal transfer. However, its simulation is a challenging problem due to surface asperities covering a wide range of length-scales. In addition, non-linear local processes, such as plasticity, are expected to occur even at the lightest loads. In this context, robust and efficient computational approaches are required. We therefore present a novel numerical method, based on integral equ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
36
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 76 publications
0
36
0
1
Order By: Relevance
“…Second, in a previous study [9], it was found that the wear coefficient cannot simply be derived only from the assumption that contact spots larger than a critical value form wear particles, while smaller ones deform plastically [16]. Indeed, this view misses important complexities, such as interactions between contact spots [68], plastic deformations due to the normal load [25,[69][70][71][72], and, as the present paper indicates, slip. This slip depends on the strength of the adhesive bond and the sharpness of the interface, and as such is subject to time-dependent phenomena such as aging [73][74][75] and interface creep [76][77][78][79].…”
Section: Discussionmentioning
confidence: 64%
“…Second, in a previous study [9], it was found that the wear coefficient cannot simply be derived only from the assumption that contact spots larger than a critical value form wear particles, while smaller ones deform plastically [16]. Indeed, this view misses important complexities, such as interactions between contact spots [68], plastic deformations due to the normal load [25,[69][70][71][72], and, as the present paper indicates, slip. This slip depends on the strength of the adhesive bond and the sharpness of the interface, and as such is subject to time-dependent phenomena such as aging [73][74][75] and interface creep [76][77][78][79].…”
Section: Discussionmentioning
confidence: 64%
“…The conjugate gradient method (CGM) has been widely accepted for the minimization, providing that the influence coefficient (IC) or the Green's function, defined as the response of displacement to a point load, has been obtained in advance. To accelerate the calculation of deformation, fast Fourier transform (FFT) technique has been employed and efforts have been made to further improve its computational efficiency [629]. A numerical scheme known as the Sami-analytical method (SAM) has been developed in last decades, in which the ICs are derived analytically in frequency space and deformations are calculated by the FFT technique.…”
Section: Progresses In Numerical Methodsmentioning
confidence: 99%
“…In this case, volume integral methods can be employed to account for plastic deformation (Telles & Brebbia, 1979). These enjoy properties analogous to boundary integral methods and can also be accelerated with a Fourier approach (Frérot et al, 2019b).…”
mentioning
confidence: 99%
“…Tamaas is a C++ library with a Python interface (Jakob, Rhinelander, & Moldovan, 2017), developed in the Computational Solid Mechanics Laboratory at EPFL, that implements a unique Fourier-accelerated volume integral formulation of equilibrium (Frérot et al, 2019b) for the solution of elastic-plastic rough contact problems. The use of C++ allows for a particular focus on performance: most loops are parallelized using Thrust/OpenMP and the fast-Fourier transforms are computed with FFTW3/OpenMP.…”
mentioning
confidence: 99%
See 1 more Smart Citation